2013
DOI: 10.1155/2013/402585
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Conditions in Tinnitus and Implications for Korean Medicine

Abstract: Tinnitus patients suffer from not only auditory sensations but also physical, mental, and social difficulties. Even though tinnitus is believed to be associated with the autonomic nervous system, changes in autonomic conditions in tinnitus patients are not receiving much research attention. The aims of this study were to investigate the autonomic condition of tinnitus patients and to consider Korean medicine in the treatment of tinnitus with an evidence-based approach. We performed a retrospective chart review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
0
20
1
1
Order By: Relevance
“…The associations between sleep apnea syndrome and its consequences could be explained by several pathophysiological mechanisms, including cardiovascular variability, intrathoracic pressure changes, inflammation, and elevated sympathetic activity . Previous research has also shown that tinnitus could chronically induce sympathetic overactivity . Therefore, it is plausible that sleep apnea‐related increase in sympathetic activity and cochlea and/or brain hypoxia could play a role in the pathogenesis of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between sleep apnea syndrome and its consequences could be explained by several pathophysiological mechanisms, including cardiovascular variability, intrathoracic pressure changes, inflammation, and elevated sympathetic activity . Previous research has also shown that tinnitus could chronically induce sympathetic overactivity . Therefore, it is plausible that sleep apnea‐related increase in sympathetic activity and cochlea and/or brain hypoxia could play a role in the pathogenesis of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…33 Previous research has also shown that tinnitus could chronically induce sympathetic overactivity. [34][35][36] Therefore, it is plausible that sleep apnea-related increase in sympathetic activity and cochlea and/or brain hypoxia could play a role in the pathogenesis of tinnitus. The strengths of this study included the large sample size, and that the diagnoses of sleep disturbance and sleep apnea were collected before that of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with tinnitus suffer from not only auditory dysfunction, but also physical, mental, and social difficulties. Patients with tinnitus also often have symptoms consistent with vagal withdrawal and sympathetic overactivity (2). Many factors have been reported to be related with the occurrence and/or severity of auditory tinnitus.…”
mentioning
confidence: 99%
“…Any individual treatment for this complex disease may not achieve a satisfactory result. Thus, combined therapy, including tinnitus retraining therapy (TRT), sound therapy, acupuncture and/or psychotherapy, are applied in patients with chronic tinnitus (2,(6)(7)(8). TRT, which includes directive counseling and sound therapy, is used by patients with chronic tinnitus with success (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation